2019
DOI: 10.1371/journal.pone.0212296
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of integrated, multilevel care for cardiovascular diseases (CVD) and HIV in low- and middle-income countries (LMICs): A scoping review

Abstract: Background Integrated cardiovascular disease (CVD) and HIV (CVD-HIV) care interventions are being adopted to tackle the growing burden of noncommunicable diseases (NCDs) in low-and middle-income countries (LMICs) but there is a paucity of studies on the feasibility of these interventions in LMICs. This scoping review aims to present evidence of the feasibility of integrated CVD-HIV care in LMICs, and the alignment of feasibility reporting in LMICs with the existing implementation science methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…To be successful, interventions must be designed to reach the population of interest; however, most importantly, they must be based on a rigorous theoretical underpinning to explain why they may succeed or fail (Nilsen, 2015). Only when interventions are targeted specifically within the socio‐environmental setting for which they are intended will implementation succeed (Lizarondo et al, 2019; Ojo et al, 2019). This concept was supported by an umbrella review of 67 systematic reviews that found that the EPOC framework enabled different intervention types to be classified and mapped to common and effective interventions (Johnson & May, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be successful, interventions must be designed to reach the population of interest; however, most importantly, they must be based on a rigorous theoretical underpinning to explain why they may succeed or fail (Nilsen, 2015). Only when interventions are targeted specifically within the socio‐environmental setting for which they are intended will implementation succeed (Lizarondo et al, 2019; Ojo et al, 2019). This concept was supported by an umbrella review of 67 systematic reviews that found that the EPOC framework enabled different intervention types to be classified and mapped to common and effective interventions (Johnson & May, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Low-to-middle income countries (LMICs) experience a high burden of disease from both non-communicable and communicable diseases (Ojo et al, 2019). Addressing these public health concerns requires effective implementation strategies and localization of translation of knowledge into practice (Edwards, Zweigenthal, & Olivier, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[163][164][165][166][167][168][169] Different projects have been working towards improving the health system, at all levels (primary care, hospitals or specialized institutes) and working with all stakeholders (health workers, managers, regional health directors) to improve access to care, increase availability and affordability of medicines, improve coordination of care or improve patient satisfaction. [170][171][172][173] Given the comorbidity between mental health and cardiometabolic conditions, some projects have promoted the opportunistic screening of mental health disorders in this group of patients and their referral using existing resources. 174 Other ongoing initiatives are using mHealth technologies to treat mild to moderate depressive symptoms among patients with cardiometabolic conditions.…”
Section: Improving Healthcarementioning
confidence: 99%
“…[9, 10] There is little understanding of how HIV clinics in SSA countries operationalize, build, and maintain capacity, particularly as it relates to translation of EBIs into practice. [11] Because of the dynamic nature of the contexts of HIV care in SSA, an assessment of the capacity of HIV clinics to manage NCDs may provide stakeholders with the knowledge needed for a systematic planning of its implementation.…”
Section: Introductionmentioning
confidence: 99%